Aplicação foliar de diferentes fontes de magnésio e interação entre absorção e partição em citros - Lucena, Vitor Hugo Silva de (Universidade Federal de São Carlos, 2025)
The project aimed to evaluate the interaction between magnesium (Mg) absorption and partitioning under different nutrient availabilities and sources in a protected cultivation system at the Sylvio Moreira Citrus Research Center, using ‘Pêra’ sweet orange [Citrus × sinensis (L.) Osbeck] seedlings grafted onto Sunki mandarin [Citrus × sunki Hort. ex Tanaka]. The experiment consisted of treatments with magnesium sulfate (MgSO₄) and magnesium nitrate (Mg(NO₃)₂) at low (125 mg L⁻¹), adequate (500 mg L⁻¹), and high (2000 mg L⁻¹) doses, arranged in a completely randomized double factorial design with five replicates. In addition, magnesium phosphite (Mg₃(PO₃)₂) was applied at a single adequate dose (500 mg L⁻¹) in a completely randomized design, with five replicates per treatment. Magnesium applications for the different experimental designs were carried out via foliar spraying, with a quarterly interval between the three applications. Analyses began after the emergence of the first vegetative flush, including measurements of chlorophyll content (SPAD), fluorimetric analyses, and leaf sampling one day after application for enzymatic extract preparation and subsequent quantification of the enzymes superoxide dismutase (SOD, EC 1.15.1.1), catalase (CAT, EC 1.11.1.6), and peroxidase (POD, EC 1.11.1.7). A marked increase in CAT and POX enzyme activity was observed at the 2000 mg L⁻¹ dose of the sulfate source. Therefore, it is concluded that foliar applications at high Mg concentrations promote the activation of enzymatic activities (CAT and POX) and ensure an efficient photosynthetic apparatus, reducing reactive oxygen species (ROS) and malondialdehyde (MDA) content.
Foliar application of different magnesium sources and the interaction between absorption and partitioning in citrus.
Keywords: Marcadores bioquímicos; Atividade enzimática; Aparato fotossintético; Parâmetros fluorimétricos; Biochemical markers; Enzymatic activity; Photosynthetic apparatus; Fluorimetric parameters; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; 12. Consumo e Produção Responsáveis